To move or to evolve: contrasting patterns of intercontinental connectivity and climatic niche evolution in “Terebinthaceae” (Anacardiaceae and Burseraceae) - Weeks, Andrea; Zapata, Felipe; Pell, Susan K.; Daly, Douglas C.; Mitchell, John D.; Fine, Paul V. A. (Frontiers in Genetics, 2014)
Many angiosperm families are distributed pantropically, yet for any given continent little is known about which lineages are ancient residents or recent arrivals. Here we use a comprehensive sampling of the pantropical sister pair Anacardiaceae and Burseraceae to assess the relative importance of continental vicariance, long-distance dispersal and niche-conservatism in generating its distinctive pattern of diversity over time. Each family has approximately the same number of species and identical stem age, yet Anacardiaceae display a broader range of fruit morphologies and dispersal strategies and include species that can withstand freezing temperatures, whereas Burseraceae do not. We found that nuclear and chloroplast data yielded a highly supported phylogenetic reconstruction that supports current taxonomic concepts and time-calibrated biogeographic reconstructions that are broadly congruent with the fossil record. We conclude that the most recent common ancestor of these families was widespread and likely distributed in the Northern Hemisphere during the Cretaceous and that vicariance between Eastern and Western Hemispheres coincided with the initial divergence of the families. The tempo of diversification of the families is strikingly different. Anacardiaceae steadily accumulated lineages starting in the Late Cretaceous–Paleocene while the majority of Burseraceae diversification occurred in the Miocene. Multiple dispersal- and vicariance-based intercontinental colonization events are inferred for both families throughout the past 100 million years. However, Anacardiaceae have shifted climatic niches frequently during this time, while Burseraceae have experienced very few shifts between dry and wet climates and only in the tropics. Thus, we conclude that both Anacardiaceae and Burseraceae move easily but that Anacardiaceae have adapted more often, either due to more varied selective pressures or greater intrinsic lability.